Short communication: Prevalence and antibiotic resistance of Staphylococcus aureus isolated from bovine clinical mastitis - Jamali, H.; Radmehr, B.; Ismail, S. (American Dairy Science Association, 2014)
The aims of this study were to determine the prevalence and antibiotic resistance of Staphylococcus aureus isolated from bovine clinical mastitis in Varamin, Tehran Province, Iran. All of the isolated Staph. aureus were identified by morphology and culture and confirmed using the API Staph identification system (bioMérieux, Marcy-l’Étoile, France). Antibiotic resistance genes were detected by PCR with oligonucleotide primers specific for each gene. Staphylococcus aureus was recovered from 43 of 207 (20.1%) bovine clinical milk samples. Using disk diffusion, methicillin-resistant Staph. aureus was detected in 5 of 43 (11.6%) samples. The pathogen showed high resistance against penicillin G (86%) and tetracycline (76.7%). The blaZ (penicillin) (86%), tetM (tetracycline), and ermC (erythromycin) genes (39.5% each) were the most prevalent antibiotic resistance genes. The findings of this study are useful for designing specific control programs for bovine clinical mastitis caused by Staph. aureus in this region of Iran.